On policy relevance of Ramsey tax rules - Sheikh Tareq Selim (Cardiff University, Cardiff Business School, 2006)
The Ramsey approach to optimal taxation and Ramsey tax rules have amassed substance in economic theory. However, they are often criticized on grounds of practicality, fairness, feasibility and some other aspects of designing actual tax policy. This paper presents a collection of these views; it discusses how closely or remotely Ramsey rules are followed in designing tax policy. It presents some recent tax reforms in the US and in the UK that have closely, if not completely, followed the principle of distortion minimization. Despite the widely speculated difficulty associated with mapping normative tax rules into positive policy design, it is possible to implement taxes that have strong correspondence to Ramsey tax formulas. This paper also discusses why some implemented tax rules lack onsistency with Ramsey principles, or why it is often difficult to establish correspondence between some implemented taxes and Ramsey tax rules.
Keywords: E61; E62; H21; H30; 330